When promises reach boundaries: political participation in post-communist countries. Issue 2 (15th March 2023) - Gherghina, Sergiu; Ekman, Joakim; Podolian, Olena
ABSTRACT: Political participation increased and diversified in the post-communist world in the last decade. This may create great expectations in terms of societal impact. This Special Section seeks to understand the complexity of this picture by analyzing instances in which the promises of political participation reach boundaries in post-communist countries. It aims to achieve two theoretical and empirical objectives. It outlines several theoretical frameworks that can be used to understand who participates and why they do so, and to identify and explain various ways in which individuals engage in politics, what are their reasons and with what expectations. The articles in this Special Section cover a range of post-communist countries in the form of comparative perspectives across countries with contextualized case studies (Bosnia and Herzegovina, Bulgaria, Georgia and Hungary) and use both qualitative and quantitative analyses.